Using the North Dakota IIS to Assess the Response of Health Care Providers to the ACIP Recommendation for Tdap Vaccination During Pregnancy. Issue 2 (March 2020) - Woinarowicz, Mary; Howell, Molly
Abstract : Objectives: To evaluate the response of North Dakota health care providers to follow the recommendation set forth by the Advisory Committee on Immunization Practices (ACIP) to administer a dose of tetanus, diphtheria, and acellular pertussis (Tdap) vaccine to women during each pregnancy using the North Dakota Immunization Information System (NDIIS). Methods: Data from the NDIIS for North Dakota infants born during calendar years 2013-2018 were extracted. Mother's name was taken from the newborn records and matched to NDIIS female client records to identify the population of mothers of newborns who would have been recommended to receive Tdap during their pregnancy. Doses of Tdap vaccine administered after October 1, 2012, were extracted from the NDIIS, and the dose records were matched back to the mother's record. The time from baby's birthdate back to the doses of Tdap vaccine administered to the mother was measured to find any doses that would have been administered during pregnancy. Results: The percentage of women receiving Tdap vaccine during pregnancy increased from 31.5% in 2013 to 60.6% in 2018. Of those women who received Tdap during pregnancy, 94% received the vaccine during the ACIP-recommended interval of 27 to 36 weeks' gestation, using the assumption that all babies were born at 40 weeks' gestation. Conclusions: North Dakota health care providers have responded positively to the recommendation of the ACIP to administer a dose of Tdap vaccine to women during each pregnancy and have increased their administration of the vaccine to their patients.